T-cell homeostasis in pediatric multiple sclerosis: old cells in young patients - Balint, Bettina; Haas, Jürgen; Schwarz, Alexander; Jarius, Sven; Fürwentsches, Alexandra; Engelhardt, Kathrin; Bußmann, Cornelia; Ebinger, Friedrich; Fritzsching, Benedikt; Paul, Friedemann; Seidel, Ulrich; Vlaho, Stefan; et al. (Neurology, 2013)
Objective: To assess pediatric patients with multiple sclerosis (MS) for early signs of homeostatic and functional abnormalities in conventional (Tcon) and regulatory T cells (Treg). - Methods: We studied the composition of the peripheral T-cell compartment and Treg function in a cross-sectional study with 30 pediatric MS (pMS) patients by multicolor flow cytometry and proliferation assays. Data were compared to those obtained from adult patients (n 5 26) and age-matched control donors (n 5 67). - Results: Proportions of naive T cells were 10%-20% higher in children than in adults, reflecting the age-related decline. pMS patients, however, had clearly lower numbers of naive T cells, among them recent thymic emigrants (RTE), whereas percentages of memory T cells were increased. In the Treg compartment, reduced RTE numbers coincided with markedly dampened suppressive capacities of total Treg. These homeostatic changes in circulating T cells precisely paralleled the pattern seen in adult MS. As in adults, treatment with immunomodulatory drugs attenuated these alterations. - Conclusion: The homeostatic changes detected in the T-cell compartment in pMS are similar to those in adult-onset disease. With ratios between naive and memory T-cell subsets matching those of 20- to 30-years-older controls, signs of early thymic involution are already found in pMS, suggesting that an intrinsic compromise in thymic-dependent T-cell neogenesis might contribute to MS pathogenesis. Neurologyâ 2013;81:784-792